Non-thermal emission from massive star-forming regions: a possible SNR candidate G351.7–1.2?. Issue 4 (10th November 2018) - Veena, V S; Vig, S; Sebastian, B; Lal, D V; Tej, A; Ghosh, S K
ABSTRACT: We present low-frequency wideband observations (300−500 MHz) of the star-forming complex G351.7–1.2 using upgraded Giant Metrewave Radio Telescope (uGMRT), India. Combining this with the optical, infrared, and submillimetre data, we analyse the large-scale diffuse radio emission associated with the region that exhibits a broken shell morphology. The spectral index of the emission in the shell is −0.8, indicating non-thermal emission. H α emission that mimics the morphology of the radio shell on a smaller scale is also detected here. Based on the non-thermal emission from the radio shell and the presence of its optical counterpart, we classify G351.7–1.2 as a candidate supernova remnant (SNR). A γ-ray source detected by Fermi LAT (1FGLJ1729.1–3641c) is located towards the south-west of the radio shell and could have a possible origin in the interaction between high-velocity particles from the SNR and the ambient molecular cloud.